2016
DOI: 10.3945/ajcn.115.130021
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium and incident type 2 diabetes: the Atherosclerosis Risk in Communities (ARIC) study

Abstract: Background: Elevated serum calcium has been associated with a variety of metabolic abnormalities and may be associated with a greater risk of diabetes. Objective: The purpose of this study was to test the hypothesis that serum calcium concentration is positively and independently associated with the incidence of diabetes and to evaluate the association of calcium-sensing receptor (CaSR) gene single nucleotide polymorphism (SNP) rs1801725 with incident diabetes. Design: Atherosclerosis Risk in Communities study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…Sing et al followed up 6096 participants for 59,130.9 persons-years while measuring serum total calcium and ACCA and found an association between elevated serum calcium concentration and incident diabetes 23 . Rooney et al also obtained the same result by following 1516 participants for an average of 8.8 years 24 . There are three possible mechanisms to explain this result.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Sing et al followed up 6096 participants for 59,130.9 persons-years while measuring serum total calcium and ACCA and found an association between elevated serum calcium concentration and incident diabetes 23 . Rooney et al also obtained the same result by following 1516 participants for an average of 8.8 years 24 . There are three possible mechanisms to explain this result.…”
Section: Discussionmentioning
confidence: 57%
“…There are three possible mechanisms to explain this result. First, serum calcium is associated with insulin resistance in adipocytes and skeletal muscle as a result of a decreased number of glucose transporters 24,25 . Calcium-dependent enzymes and calcium channels are responsible for glucose uptake after insulin stimulates muscle cells 12,26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found associations between high levels of calcium in the blood and risk of developing T2DM. Such studies include the PREDIMED study [74], the Atherosclerosis Risk in Communities (ARIC) study [75], the Insulin Resistance Atherosclerosis study [76] and the TromsĂž study [77]. In addition, elevated total plasma calcium levels are also found in individuals with T2DM compared to healthy controls; no difference was observed between males and females and the duration of diabetes had no influence on calcium levels [78].…”
Section: Changes In Metal Ion Homeostasismentioning
confidence: 99%
“…However, obesity continues to be a serious health issue in the United States, and preventive efforts have not been fruitful. In addition to obesity, other risk factors, such as the one suggested by Rooney et al (1) in this issue of the Journal, imply opportunities for the development of new prevention strategies. In this study, the investigators evaluated serum calcium as a potential risk factor for incident diabetes in a large biracial prospective cohort from the ARIC (Atherosclerosis Risk in Communities) study.…”
mentioning
confidence: 99%